Analysis Of Hazardous Heavy Metal Content in Maritime Ecosystems - Fitriani Putri; Pardi Hilfi; Jordan Laila (BIO Web of Conferences)
Maritime ecosystems, rich in diverse biota and natural resources, are an essential element in maintaining global ecological balance. However, the sustainability of these ecosystems is threatened by harmful heavy metal contamination, which can jeopardize the health of maritime ecosystems and the well-being of humans who rely heavily on marine resources. This study aims to identify heavy metal content in the maritime environment. Using a literature review method on data from 2019 to 2023, it was analyzed and corroborated with journal articles. The results highlighted nine hazardous heavy metals, such as copper, lead, cadmium, zinc, chromium, nickel, iron, manganese and mercury, which are capable of contaminating seawater and causing toxic effects on marine organisms. Therefore, serious efforts are needed to reduce and manage heavy metal contamination in the maritime environment to maintain ecosystem sustainability and protect the well-being of humans who depend on marine resources